A solid superacid, a proton conductor ceramic based on the solid superacid and its application
By using solid super acid WO3/ZrO2 to prepare proton conductor ceramics, the problem of insufficient stability and conductivity of existing proton conductors at high temperatures is solved, and a proton conductor ceramic with high proton conductors in the range of 100-300℃ is realized, which promotes the development of high-temperature proton exchange membrane fuel cells.
Patent Information
- Application Number
- CN202210737432.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-06-27
AI Technical Summary
Existing proton conductors cannot have high proton conductivity and stability within the temperature range of 100-300℃, which limits the development of high-temperature proton exchange membrane fuel cells.
Solid super acid WO3/ZrO2 is used as the basic material of proton conductor ceramics. Proton conductor ceramics with high proton conductors are prepared by wet ball milling with zirconium salt and ammonium metatungstate in alcohol and calcining at high temperature.
It significantly improves the proton conductivity and stability of proton conductor ceramics, is suitable for temperature range of 100-300℃, has excellent thermal stability, chemical stability and mechanical properties, and is suitable for electrochemical devices such as fuel cells and electrolytic cells.
Smart Images

Figure CN115101792B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a solid superacid, a proton conductor ceramic based on the solid superacid and applications thereof. Background Art
[0002] Proton exchange membrane fuel cell (PEMFC) is an energy conversion device that converts the chemical energy of hydrogen into electrical energy. It is the core energy conversion device in the hydrogen energy utilization system. At present, the operating temperature of PEMFC is below 100°C and is highly dependent on Pt-based catalysts. However, the global annual production of Pt is only about 180 tons. The shortage of precious metal Pt is an insurmountable obstacle to the development of PEMFC. Secondly, the proton exchange membrane used in PEMFC is mainly perfluorosulfonic acid resin material, which has good proton conductivity only at high humidity, which increases the complexity of the fuel cell system.
[0003] Increasing the operating temperature of PEMFC (100-300℃) can improve the kinetics of oxygen reduction reaction, thereby reducing the amount of Pt used and even using non-precious metals as catalysts, reducing catalyst costs; at the same time, water exists in gaseous form above 100℃, which can simplify the water management system and reduce water management costs; increasing the tolerance of catalysts to impurity gases such as CO can reduce fuel costs. Based on the above advantages, the development of high-temperature PEMFC can promote the development of fuel cells.
[0004] The key to increasing the operating temperature of PEMFC is to develop suitable proton conductors. Among the various proton conductors studied so far, only inorganic proton conductors are practically feasible. At present, the inorganic proton conductors that are studied more are acid salts, heteropoly acids, and perovskite-type proton conductors. However, acid salt and heteropoly acid proton conductors face problems such as poor thermal stability and narrow operating temperature range. Although perovskite-type proton conductors have good stability, they need to have high proton conductivity at high temperatures (>600°C). Therefore, the development of new inorganic proton conductors with good stability and proton conductivity at 100-300°C is of great practical significance. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a solid superacid, a proton conductor ceramic based on the solid superacid and its application, and solve the technical problem in the prior art that the proton conductor cannot have both high proton conductivity and stability in the temperature range of 100-300°C.
[0006] The first aspect of the present invention provides a method for preparing a solid superacid WO3 / ZrO2, comprising the following steps:
[0007] The zirconium salt and ammonium metatungstate are dispersed in alcohol, mixed evenly by wet ball milling, and then the solvent is removed. The mixture after the solvent is removed is calcined at high temperature to obtain solid superacid WO3 / ZrO2; wherein the molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate is 4-35:1; the calcination temperature is 600-700°C, the insulation time is 1-6h, and the calcination atmosphere is air or oxygen.
[0008] The second aspect of the present invention provides a solid super acid WO3 / ZrO2, which is obtained by the preparation method of the solid super acid WO3 / ZrO2 provided by the first aspect of the present invention.
[0009] A third aspect of the present invention provides a method for preparing a proton conductor ceramic based on a solid superacid, comprising the following steps:
[0010] The solid superacid WO3 / ZrO2 and carbonate are uniformly mixed and then calcined at high temperature to obtain a proton conductor powder;
[0011] The proton conductor powder is pressed into an electrolyte sheet and then sintered at high temperature to obtain a proton conductor ceramic;
[0012] The above-mentioned solid super acid WO3 / ZrO2 is the solid super acid WO3 / ZrO2 provided by the second aspect of the present invention; the carbonate is at least one of Li2CO3, K2CO3, and Na2CO3; the mass of the carbonate accounts for 10% to 50% of the total mass of the mixture of the solid super acid WO3 / ZrO2 and the carbonate.
[0013] The fourth aspect of the present invention provides a proton conductor ceramic based on a solid superacid, and the proton conductor ceramic based on a solid superacid is obtained by the preparation method of the proton conductor ceramic based on a solid superacid provided by the third aspect of the present invention.
[0014] A fifth aspect of the present invention provides an application of a proton conductor ceramic based on a solid superacid, wherein the proton conductor ceramic based on a solid superacid is applied as an electrolyte material of a proton conductor fuel cell or an electrolytic cell.
[0015] Compared with the prior art, the beneficial effects of the present invention include:
[0016] The preparation method of the solid superacid WO3 / ZrO2 of the present invention is simpler and more convenient than the previous method, greatly shortening the time for preparing the solid superacid WO3 / ZrO2, and the proton conductor ceramic made of the solid superacid WO3 / ZrO2 prepared by the method has significantly higher proton conductivity and better stability than other methods;
[0017] The proton conductor ceramic preparation method based on solid superacid WO3 / ZrO2 of the present invention is simple and low-cost, has excellent thermal stability, chemical stability and mechanical properties, and has excellent proton conductivity in the temperature range of room temperature to 300°C. The ultra-wide operating temperature range makes it likely to be widely used in related electrochemical devices such as fuel cells, electrolytic cells, sensors, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 XRD patterns of ZrO2 prepared by calcining at 450°C and 650°C without adding W and solid superacid WO3 / ZrO2 prepared by calcining at 450°C with a Zr:W molar ratio of 7.5:1;
[0019] Figure 2 XRD patterns of solid superacid WO3 / ZrO2 prepared by calcining at 650℃ with different Zr:W molar ratios;
[0020] Figure 3 The XRD spectra of the mixture of Li2CO3 and K2CO3, the mixture of Li2CO3 and Na2CO3, and the proton conductor powder synthesized in Example 4. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0022] The first aspect of the present invention provides a method for preparing a solid superacid WO3 / ZrO2, comprising the following steps:
[0023] The zirconium salt and ammonium metatungstate are dispersed in alcohol, and mixed evenly by wet ball milling. The solvent is then removed, and the mixture after the solvent is removed is calcined at high temperature to obtain a solid superacid WO3 / ZrO2.
[0024] In the present invention, the molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate is 4-35:1, further 4.4-16.9:1, further 5-10:1, further 7.5:1.
[0025] In the present invention, the zirconium salt is at least one of zirconium oxychloride, zirconyl nitrate and zirconyl sulfate.
[0026] In the present invention, the alcohol is isopropanol or propanol.
[0027] In the present invention, the usage ratio of zirconium salt to alcohol is 1g:1-5ml.
[0028] In some specific embodiments of the present invention, the ball milling time is 1-3 h.
[0029] In some embodiments of the present invention, the solvent is removed by drying the wet ball-milled mixture in a forced air drying oven.
[0030] In the present invention, during the high-temperature calcination of the mixture after the solvent is removed: the calcination temperature is 600-700°C, further 650°C; the insulation time is 1-6h, further 1h; the calcination atmosphere is air or oxygen, and the heating rate is 1-5°C / min, further 1°C / min.
[0031] The second aspect of the present invention provides a solid super acid WO3 / ZrO2, which is obtained by the preparation method of the solid super acid WO3 / ZrO2 provided by the first aspect of the present invention.
[0032] A third aspect of the present invention provides a method for preparing a proton conductor ceramic based on a solid superacid, comprising the following steps:
[0033] The solid superacid WO3 / ZrO2 and carbonate are uniformly mixed and then calcined at high temperature to obtain a proton conductor powder;
[0034] The proton conductor powder is pressed into an electrolyte sheet and then sintered at high temperature to obtain a proton conductor ceramic.
[0035] In some preferred embodiments of the present invention, the solid superacid WO3 / ZrO2 is the solid superacid WO3 / ZrO2 provided in the second aspect of the present invention. The inventors have found that the solid superacid WO3 / ZrO2 prepared by the present invention is more conducive to improving the conductivity and stability of the proton conductor ceramic.
[0036] In the present invention, the carbonate is at least one of Li2CO3, K2CO3, and Na2CO3, preferably a mixture of Li2CO3 and K2CO3, more preferably a mixture of Li2CO3 and K2CO3 in a molar ratio of 1:(0.5-1), and more preferably a mixture of Li2CO3 and K2CO3 in a molar ratio of 31:19.
[0037] In the present invention, the mass of carbonate accounts for 10% to 50% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate, further 10% to 40%, and further 20 to 30%.
[0038] In some specific embodiments of the present invention, the solid superacid WO3 / ZrO2 and the carbonate are uniformly mixed by mortar grinding or dry ball milling.
[0039] In the present invention, during the process of high-temperature calcination after the solid super acid WO3 / ZrO2 and carbonate are evenly mixed: the calcination temperature is 600-800°C, further 650°C; the insulation time is 1-24h, further 3h; the calcination atmosphere is air or oxygen, and the heating rate is 1-10°C / min, further 5°C / min.
[0040] In the present invention, the step of pressing the proton conductor powder into an electrolyte sheet specifically comprises: pressing the proton conductor powder into an electrolyte sheet at 200-1000 MPa.
[0041] In the present invention, during the high-temperature sintering process after the proton conductor powder is pressed into an electrolyte sheet: the sintering temperature is 600-800°C, further 650°C; the insulation time is 1-12h, further 3h, the sintering atmosphere is air or oxygen, and the heating rate is 1-10°C / min, further 5°C / min.
[0042] The fourth aspect of the present invention provides a proton conductor ceramic based on a solid superacid, and the proton conductor ceramic based on a solid superacid is obtained by the preparation method of the proton conductor ceramic based on a solid superacid provided by the third aspect of the present invention.
[0043] A fifth aspect of the present invention provides an application of a proton conductor ceramic based on a solid superacid, wherein the proton conductor ceramic based on a solid superacid is applied as an electrolyte material of a proton conductor fuel cell or an electrolytic cell.
[0044] Example 1
[0045] In this embodiment, the molar ratio of zirconium atoms to tungsten atoms in zirconium salt and ammonium metatungstate is 7.5:1, the mass of carbonate accounts for 30% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate, and the carbonate is Li2CO3. Specifically, the following steps are included:
[0046] (1) 4 g of zirconium oxychloride octahydrate (ZrOCl2·8H2O, molecular weight 322.25) and 0.4063 g of ammonium metatungstate ((NH4)6H2W 12 O 40 xH2O, molecular weight 2956.3) was dispersed in 10 ml of isopropanol, ball-milled for 2 h, mixed evenly, and then placed in a blast drying oven for 6 h to remove the isopropanol. The product after the solvent was removed was placed in a tube furnace and heated to 650°C at a rate of 1°C / min in an air atmosphere, kept warm for 1 h, and finally cooled naturally to room temperature to obtain a solid superacid WO3 / ZrO2;
[0047] (2) Grinding the solid superacid WO3 / ZrO2 and the carbonate in a mortar and mixing them uniformly, then placing them in a tube furnace, heating them to 650°C at a rate of 5°C / min in an air atmosphere, keeping the temperature for 3 hours, and finally cooling them naturally to room temperature to obtain a proton conductor powder;
[0048] (3) The proton conductor powder was pressed into a disc with a diameter of 13 mm and a thickness of 1 mm at 800 MPa, and then placed in a tubular furnace. In an air atmosphere, the temperature was raised to 650°C at a rate of 5°C / min, kept at that temperature for 3 h, and finally naturally cooled to room temperature to obtain a proton conductor ceramic based on solid superacid WO3 / ZrO2.
[0049] Example 2
[0050] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 1, except that the carbonate in this embodiment is K2CO3.
[0051] Example 3
[0052] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 1, except that the carbonate in this embodiment is Na2CO3.
[0053] Example 4
[0054] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 1, except that the carbonate in this embodiment is a mixture of Li2CO3 and K2CO3, and the molar ratio of Li2CO3 to K2CO3 is 31:19.
[0055] Example 5
[0056] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 4, except that the carbonate in this embodiment is a mixture of Li2CO3 and Na2CO3, and the molar ratio of Li2CO3 to Na2CO3 is 13:12.
[0057] Example 6
[0058] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Embodiment 4, except that the mass of carbonate in this embodiment accounts for 50% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate.
[0059] Example 7
[0060] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 4, except that in this embodiment, the mass of carbonate accounts for 10% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate.
[0061] Example 8
[0062] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Example 4, except that the molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate in this embodiment is 16.9:1.
[0063] Example 9
[0064] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Embodiment 4, except that the molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate in this embodiment is 4.4:1.
[0065] Comparative Example 1
[0066] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Embodiment 1, except that the carbonate doping amount in this embodiment is 0.
[0067] Comparative Example 2
[0068] The preparation process of the solid superacid WO3 / ZrO2 proton conductor ceramic in this embodiment is the same as that in Embodiment 4, except that the amount of ammonium metatungstate added in this embodiment is zero.
[0069] Comparative Example 3
[0070] In this comparative example, the molar ratio of zirconium atoms to tungsten atoms in zirconium salt and ammonium metatungstate is 7.5:1, the mass of carbonate accounts for 30% of the total mass of the mixture of solid super acid WO3 / ZrO2 and carbonate, and the carbonate is a mixture of Li2CO3 and K2CO3, and the molar ratio of Li2CO3 to K2CO3 is 31:19. The only difference is that the preparation process of solid super acid WO3 / ZrO2 in this comparative example adopts the traditional impregnation method. Specifically, it includes the following steps:
[0071] (1) 4 g of zirconium oxychloride octahydrate (ZrOCl2·8H2O, molecular weight 322.25) was dissolved in 100 ml of deionized water, and ammonia water was added to adjust the pH of the solution to 9. The solution was aged at room temperature for 24 h, and then filtered and washed. The obtained white precipitate was dried at 110° C. for 12 h, and ground to obtain white zirconium hydroxide powder;
[0072] (2) 0.4112 g of ammonium metatungstate ((NH4)6H2W 12 O 40xH2O, molecular weight 2956.3) was dissolved in 30 ml of deionized water, and then 2 g of zirconium hydroxide (Zr(OH)4, 159.25) powder was added, and after impregnation for 6 h, it was dried at 80 ° C for 12 h, and then placed in a tube furnace, and heated to 650 ° C at a rate of 5 ° C / min in an air atmosphere, and kept warm for 3 h, and finally cooled naturally to room temperature to obtain a solid super acid WO3 / ZrO2;
[0073] (3) Grinding the solid superacid WO3 / ZrO2 and the carbonate in a mortar and mixing them uniformly, then placing them in a tube furnace, heating them to 650°C at a rate of 5°C / min in an air atmosphere, keeping the temperature for 3 hours, and finally cooling them naturally to room temperature to obtain a proton conductor powder;
[0074] (4) The proton conductor powder was pressed into a disc with a diameter of 13 mm and a thickness of 1 mm at 800 MPa, and then placed in a tubular furnace. In an air atmosphere, the temperature was raised to 650°C at a rate of 5°C / min, kept at that temperature for 3 h, and finally naturally cooled to room temperature to obtain a proton conductor ceramic based on solid superacid WO3 / ZrO2.
[0075] Experimental Group 1
[0076] The crystal phase tests were conducted on ZrO2 prepared at different calcination temperatures and solid superacid WO3 / ZrO2 with different Zr:W molar ratios. The test results are shown in Figure 1 and 2 Among them, the calcination time is 1h.
[0077] Figure 1 XRD patterns of ZrO2 prepared by calcining at 450°C and 650°C without adding W and solid superacid WO3 / ZrO2 prepared by calcining at 450°C with a Zr:W molar ratio of 7.5:1; Figure 2 XRD patterns of solid superacid WO3 / ZrO2 prepared by calcining at 650°C with different Zr:W molar ratios. Figure 1 It can be seen that when W is not added and the calcination temperature is 450℃, the crystal form of ZrO2 is tetragonal, but when the calcination temperature is increased to 650℃, the crystal form of ZrO2 is mainly monoclinic, with only a small amount of tetragonal phase; at the same time, it can be seen that the solid superacid WO3 / ZrO2 with a Zr:W ratio of 7.5:1, when calcined at 450℃, the ZrO2 crystal form obtained shows the characteristic peaks of the tetragonal phase, but the peaks are broad, indicating that the crystallinity of ZrO2 is low, which will be unfavorable for the formation of strong acid sites. Figure 2It can be seen that after calcination at 650°C, the solid superacid WO3 / ZrO2 with different Zr:W molar ratios all showed characteristic peaks of tetragonal ZrO2 with sharp peaks, indicating that the crystallinity of ZrO2 was good; at the same time, no characteristic peaks of WO3 were observed, indicating that WO3 was highly dispersed on the surface of ZrO2, which illustrates the superiority of the method for preparing solid superacid WO3 / ZrO2 of the present invention.
[0078] Experimental Group 2
[0079] The crystal phase test was carried out on the mixture of Li2CO3 and K2CO3, the mixture of Li2CO3 and Na2CO3 and the proton conductor powder synthesized in Example 4. The test results are shown in Figure 3 . Figure 3 The XRD patterns of the mixture of Li2CO3 and K2CO3, the mixture of Li2CO3 and Na2CO3, and the proton conductor powder synthesized in Example 4 are shown in FIG. Figure 3 It can be seen that the solid superacid WO3 / ZrO2 and carbonate are not simply physically mixed but undergo a chemical reaction to generate a variety of chemical species.
[0080] Experimental Group 3
[0081] Conductivity test of different proton conductor ceramics: Silver paste was applied on both sides of the test sample and silver wire was connected as electrodes and conductors. The proton conductivity was tested using a Coster electrochemical workstation with an AC voltage of 20mV. The sample was placed in a tube furnace and tested under the condition of a 10% hydrogen-argon mixed gas humidified with 25°C water in a quartz tube. The test temperature ranged from room temperature to 300°C. The test results are shown in Table 1.
[0082] Table 1
[0083]
[0084] By comparing Examples 1-3 with Comparative Example 1, it can be seen that the addition of single carbonates Li2CO3, K2CO3, and Na2CO3 can enhance the proton conductivity of the solid superacid WO3 / ZrO2 to a certain extent, but the effect is not significant.
[0085] By comparing Examples 1-5, it can be seen that the selection of a mixed carbonate of Li2CO3 and K2CO3 not only significantly improves the proton conductivity but also significantly improves the stability, ultimately making it have a very high proton conductivity at room temperature to 300°C.
[0086] By comparing Examples 4, 6, and 7, it can be seen that when the amount of carbonate added is too much, the proton conductivity decreases. The reason may be that too much carbonate will cover the high conductive path, resulting in a decrease in proton conductivity; when the amount of carbonate added is too little, the proton conductivity also decreases. The reason may be that too little carbonate is not conducive to forming a high proton conductive path and is not conducive to improving proton conductivity.
[0087] By comparing Examples 4, 8, 9 and Comparative Example 2, it can be seen that too little W is not conducive to the formation of highly conductive materials, while too much W will affect the interaction between carbonate and zirconia matrix, which leads to a decrease in ceramic proton conductivity.
[0088] By comparing Example 4 with Comparative Example 3, it can be seen that compared with the traditional impregnation method, the proton conductor ceramic prepared by the present invention has a higher and more stable proton conductivity, which further illustrates the superiority of the present invention in preparing the solid superacid WO3 / ZrO2.
[0089] In order to further demonstrate the advantages of the present application, Table 2 lists the proton conductivity of currently common proton conductor ceramics cesium dihydrogen phosphate and perovskite.
[0090] Table 2
[0091]
[0092] It can be seen from Table 2 that cesium dihydrogen phosphate has a high proton conductivity only when it undergoes a superproton phase transition at around 243°C, but it will decompose into CsPO3 above 280°C; while perovskite-type proton conductor ceramics have good stability, but their conductivity is extremely low below 300°C, and they only have a high proton conductivity at high temperatures. The proton conductor ceramics prepared by the present invention show excellent proton conductivity in the range of room temperature to 300°C, and have advantages that the proton conductor ceramics currently studied do not have.
[0093] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a proton conductor ceramic based on a solid superacid, characterized in that: The following steps are involved: Dispersing zirconium salt and ammonium metatungstate in alcohol, mixing them evenly by wet ball milling, then removing the solvent, and calcining the mixture after removing the solvent at high temperature to obtain solid super acid WO3 / ZrO2; The solid super acid WO3 / ZrO2 is mixed evenly with carbonate and then calcined at high temperature to obtain a proton conductor powder; The proton conductor powder is pressed into an electrolyte sheet and then sintered at high temperature to obtain a proton conductor ceramic; wherein, The molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate is 4-35:1; the calcination temperature is 600-700°C, the holding time is 1-6 h, and the calcination atmosphere is air or oxygen; The carbonate is at least one of Li2CO3, K2CO3, and Na2CO3; the mass of the carbonate accounts for 10% to 50% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate.
2. The method for preparing a proton conductor ceramic based on a solid superacid according to claim 1, characterized in that: The molar ratio of zirconium atoms to tungsten atoms in the zirconium salt and ammonium metatungstate is 5-10:
1.
3. The method for preparing a proton conductor ceramic based on a solid superacid according to claim 1, characterized in that: The zirconium salt is at least one of zirconium oxychloride, zirconium oxynitrate and zirconium oxy sulfate; and the alcohol is isopropanol or propanol.
4. The method for preparing a proton conductor ceramic based on a solid superacid according to claim 1, characterized in that: The carbonate is a mixture of Li2CO3 and K2CO3 in a molar ratio of 1: (0.5-1).
5. The method for preparing a proton conductor ceramic based on a solid superacid according to claim 1, characterized in that: The mass of the carbonate accounts for 20-30% of the total mass of the mixture of solid superacid WO3 / ZrO2 and carbonate.
6. The method for preparing a proton conductor ceramic based on a solid superacid according to claim 1, characterized in that: In the process of mixing the solid super acid WO3 / ZrO2 and the carbonate uniformly and then calcining at high temperature: the calcination temperature is 600-800°C, the holding time is 1-24 h, and the calcination atmosphere is air or oxygen; In the process of high-temperature sintering after pressing the proton conductor powder into an electrolyte sheet, the sintering temperature is 600-800° C., the heat preservation time is 1-12 h, and the sintering atmosphere is air or oxygen.
7. A proton conductor ceramic based on solid superacid, characterized in that: The solid superacid-based proton conductor ceramic is obtained by the preparation method of the solid superacid-based proton conductor ceramic according to claim 1.
8. An application of the proton conductor ceramic based on solid superacid as claimed in claim 7, characterized in that: The proton conductor ceramic based on solid superacid is applied as an electrolyte material of a proton conductor fuel cell or an electrolytic cell.
Citation Information
Patent Citations
TiO2 Polycrystalline foamed ceramic catalyst, preparation method thereof and method of using catalyst to catalyze waste plastics and biodiesel to produce hydrocarbons
CN107617441A